Antioxidant, Anti-Inflammatory, and Cytotoxic Activity of Extracts from Some Commercial Apple Cultivars in Two Colorectal and Glioblastoma Human Cell Lines - Aurita Butkeviciute; Vilma Petrikaite; Vidmante Jurgaityte; Mindaugas Liaudanskas; Valdimaras Janulis (MDPI AG, 2021)
Cancer initiation and development are closely related to oxidative stress and chronic inflammation. The aim of this study was to evaluate apple extracts and individual tritepenes antioxidant, anti-inflammatory, and cytotoxic activities. Dry extracts of apple were analyzed by HPLC-PDA. A hyaluronidase inhibition assay was selected to determine the anti-inflammatory effect. Cytotoxic activities against human colon adenocarcinoma cell line (HT-29) and human glioblastoma cell line (U-87) were determined using MTT, cell colony formation, and spheroid growth assays. Radical scavenging and reducing activities were evaluated using DPPH, ABTS, FRAP, and CUPRAC assays, respectively. The apple extracts inhibited hyaluronidase from 26.38 ± 4.4% to 35.05 ± 3.8%. The AAW extract possessed the strongest cytotoxic activity (EC50 varied from 113.3 ± 11.11 µg/mL to 119.7 ± 4.0 µg/mL). The AEW extract had four and five times stronger antiradical activity when determined by ABTS and DPPH, and two and eight times stronger reducing activity when evaluated by CUPRAC and FRAP, respectively. Understanding the mechanisms of apple extracts and individual triterpenes as hyaluronidase inhibitors and antioxidants related in cancer development may be a benefit to future study in vivo, as well as cancer prognosis or the development of new, innovative food supplements, which could be used for chronic disease prevention.